Exploring the Effects of Synergistic Combustion of Alcohols and Biodiesel on Combustion Performance and Emissions of Diesel Engines: A Review - Fangyuan Zheng; Haeng Muk Cho (Energies)
Diesel engines are extensively employed in transportation, agriculture, and industry due to their high thermal efficiency and fuel economy. However, the combustion of conventional diesel fuel is accompanied by substantial emissions of pollutants, including carbon monoxide (CO), hydrocarbons (HC), nitrogen oxides (NOx), and carbon dioxide (CO2), posing significant threats to environmental quality. Biodiesel, as a renewable and cleaner alternative fuel, can significantly reduce emissions of CO, HC, and particulate matter (PM) due to its unique molecular structure. Nonetheless, its lower calorific value and poor cold-start performance limit its application, while its high oxygen content may contribute to increased NOx emissions. To address these limitations, researchers have proposed blending biodiesel with alcohol-based fuels such as methanol, ethanol, or butanol to create synergistic combustion systems that optimize engine performance and emission characteristics. This paper systematically reviews the effects of alcohol fuels on the performance and emission characteristics of biodiesel blends in diesel engines. Studies indicate that the addition of alcohol fuels can significantly enhance engine performance by improving fuel atomization, extending ignition delay, and increasing premixed combustion efficiency. These enhancements result in higher cylinder pressure, net heat release rate (HRR), and brake thermal efficiency (BTE), while reducing brake-specific fuel consumption (BSFC) to some extent. Moreover, most studies report that alcohol fuels help reduce CO, HC, smoke, and NOx emissions but tend to increase CO2 emissions. However, some findings suggest that in certain cases, the opposite results may occur. The impact of different types of alcohol fuels on performance and emissions varies significantly, requiring a comprehensive evaluation of their properties, such as latent heat, viscosity, and oxygen content. Although the appropriate addition of alcohol fuels demonstrates substantial potential for optimizing engine performance and reducing emissions, excessive blending may lead to adverse effects, necessitating careful control of the blending ratio. Future research should consider mixing two or more alcohol fuels with biodiesel to explore synergistic effects beyond the capabilities of single alcohols. Additionally, further studies should focus on optimizing fuel compositions and emission control strategies for varying operating conditions.